(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate the frequency and patterns of Magnetic Resonance Imaging (MRI) for disk degeneration in adolescence and young adults, in lumbosacral spine. Study Design: Cross-sectional study Place and Duration of Study: This study was carried out at Department of Diagnostic Imaging in Nishtar Hospital, Multan during January 2012 to December 2012. Materials and Methods: One hundred patients presented with low back pain and were advised MRI, participated in the study. Demographics were assessed by using a questionnaire and their lumbar disk T2 maps were quantified via sagittal imaging protocols at 1.5T.MRI was reported by two radiologists separately. Data was analyzed by using SPSS (v. 16) as well as manually. P values less than 0.05 were considered significant. Results: The frequency of disk degeneration was found to be 44%. Mean age of the patients was 19.47 ± 2.19 years. Mean duration of pain was 6.93 ± 1.49 months. Most patients (53%) have multilevel involvement with 31% having disease at L4-L5 level. Other significant MRI findings included disc bulge (central 46%, paracentral 29%), thecal sac compression 75% and exiting nerve root compression in 54% along with ligamentus hypertrophy 19%. The statistically significant association (p < 0.009) between desicatory changes & nerve root compression and between Pfirrmann grades & radiculopathy (p < 0.01) were noted. Conclusion: Frequency of disco-vertebral degenerative disease is significant in juveniles presenting with low back pain. So, any patient especially with chronic low back pain should undergo MRI spine for early diagnosis of degenerative disease. Moreover multilevel involvement and signs of radiculopathy are also significant.